As mudanças na organização e localização da indústria automobilística brasileira (1996-2001) - Otavio Silva Camargo (2006)
The world car industry presented historically three evolution periods. Each period has its own and distinguishing features related to the technological and organizational innovations, management of production organization, market structure and location of the companies. The period of craftsmen production (from 1894 to 1907); the period of mass production with the Fordism/Sloanism (from 1908 to 1960/70); and lean production identified with the Toyotism (from 1960/70 until now).In the 90s a strong expansion of automakers and suppliers occurred towards emergent countries due to increasing international competition. Brazil was part of this process. The restructuring of its auto industry was a result of, not only, these changes in the global industry, but also because of policy changes in the Brazilian economy. The Brazilian trade opening, the Mercosul integration and the macroeconomic reforms led to specific policies to the domestic auto industry and a new wave of technological and managerial changes and of new investments. These changes led to a transformation of the industrys market structure and location pattern.The aim of this thesis is to analyze these structural transformations in Brazilian automotive industry in this decade, mainly in its second part. The focus of the analysis is on the technological, organizational and locational transformations. The paper tried to answer the following questions: How to explain the relation between the technological and organizational changes in the Worlds market structure and spatial location pattern?What were the main changes in the Brazilian automotive industry regarding its competitive behavior and its market structure after the trade opening and new wave of investments?What the impact of these changes on the market power and concentration level of this industry and its sectors?How did the entry of world newcomers automakers or suppliers change the structures of the existing oligopoly?Were there in fact changes in the locational criteria and spatial location of this industry in Brazil?How the changes in the industrys organization in Brazil, with the hierarchy of suppliers, led to a regional concentration of productive and technological activities?The main axis of this thesis aims the understanding of the interaction between the oligopolys dynamics and the spatial dynamics. The analytical support had the theoretical tools of oligopoly theory, transaction costs economics and location theory, as well as the approach of the role of technological innovations and multinational companies to structural changes in the industry.